A lateral pós-vocálica em contato dialetal: um estudo com africanos lusófonos em João Pessoa - Silva, Paloma Freire de Queiroz e (2013)
The migration is an increasing phenomenon witnessed nowadays. Through the student program “Programa de Estudantes-Convênio de Graduação (PEC-G)”, students from developing countries have the opportunity to enrol in a under graduation course in Brazil, increasing the number of African students in Brazilian universities. The contact situation among these groups made evident dialect differences between Brazilians and luso Africans. In this work, we investigate if the Guineans and the Cape Verdeans, which live in João Pessoa present characteristics of “linguistic accommodation” to the dialect from Paraíba regarding the lateral in situation of the syllabically coda. The lateral in coda position can be produced in a velarized, vocalised or deleted manner. The vocalisation is characteristic of the Brazilian variety, while the maintenance of the lateral is characteristic of Cape Verde and Guinea-Bissau Portuguese language. It is also investigated which aspects can favour the accommodation, being it socials, stylistic, or linguistic. Moreover, it is investigated the linguistic attitude that they represent related to the origin and foreign dialect, and also the identification cultural degree related to the origin and new culture. In this study, it was applied methods of the quantitative sociolinguistic. Interviews were carried out and recorded, and words that contained pos vocal lateral were codified, and the program Goldvarb-X was used to statistical data analyses. For the qualitative analyses, it was used the concepts of accommodation theory and linguistic attitudes. The accommodation theory says that the speaker does linguistic adjusts when in contact with a different dialect. These adjusts can be in a sense of convergence, divergence or non-convergence. The theories about linguistic attitudes, for instance, state that the perceptions that a speaker has about a specific linguistic variance affect his/her linguistic choices. As result of this research, it was obtained that the Cape Verdeans have more accommodation to the João Pessoa variety then the Guineans. This result finds a possible explanation in the way each group relates with their origin country, having the Guineans a more strong identification feeling with their origin country than the Cape Verdeans. It was also found evidences that the time period that the subjects are exposed to the new dialect affect the accommodation rates. Related to the linguistic variables, among others, it was perceived that the tonic syllables favour the vocalisation, on the other hand, unstressed syllables favour the lateral maintenance. It was also noted that the respondents evaluated varieties of settler countries or more advanced regions in a positive way, while that the varieties of regions historically disadvantaged were given negative attributes. In this way, it is concluded that there is a process of accommodation among the investigated groups, corresponding to almost a third of total occurrences. Finally, it is stressed that the linguistic variation phenomenon is complex and several aspects can influence it. It was proposed in this work to analyse the influence of some variables, which were judged to affect the realisation of the lateral pos vocalic, this rol of variables, however, is not conclusive, so that, other aspects can affect the variation in study.